Effects of pretreatments on colour alterations of litchi during drying and storage - Busarakorn Mahayothee (2018)
The objective of this research was to study the effect of osmotic pretreatment with combined anti-browning agents (acid, glycerol and/or trehalose) on the colour characteristics of dried litchi after drying and during 5 months of storage compared to samples without pretreatment. The pretreated samples showed good inhibition of polyphenol oxidase activity when compared with the control, while the total phenolic contents in the dried products were not reduced. The results demonstrated that water activity, lightness difference, chroma, degree of browning (DB), and 5-hydroxymethylfurfural values of all pretreated samples increased, while hue angle decreased with storage time. Samples pretreated with glycerol showed the best potential for browning retardation, followed by glycerol combined with trehalose, and trehalose, respectively. In addition, the colour parameters were used to calculate the luminescence values, representing the data in grey scale, which were correlated with a non-enzymatic browning index. The results showed grey value could be adequately used to represent the DB of dried litchi with r2value of 0.92. © 2009 Springer-Verlag.